Scattered reflections on the Crime of Mafia association. Starting from the third edition of Giuliano Turone's book (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
An essential prerequisite for an effective action of contrast to the Mafia is a correct and complete knowledge of the same. On the legal level, a formidable contribution in this direction is offered by the Book of Giuliano Turone, published now in the third updated edition. The hallmarks of this important work are the confluence of a plurality of knowledge, legal and extragiuridic, and a convinced and motivated respect for the constitutional principles of criminal law. At the same time, these mark the tracks along which the use of legal instruments should always proceed to fight the organized crime of mafia-type.